1996
DOI: 10.1021/la951524t
|View full text |Cite
|
Sign up to set email alerts
|

Thiocholesterol on Gold:  A Nanoporous Molecular Assembly

Abstract: The formation of thiocholesterol (TC) monolayers on gold has been studied by ellipsometry, contact angle measurements, infrared spectroscopy, and cyclic voltammetry. Subsequent treatment of the TC assembly with 11-mercaptodeuterioundecanoic acid (MDUA) shows that the average surface coverage is about 65% of that of a self-assembled alkanethiolate monolayer and that it has a large number of molecular defects. These defects exist because of a mismatch between the size and shape of the TC molecule and the pinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 40 publications
(56 reference statements)
6
59
1
1
Order By: Relevance
“…There is current interest in gold and platinum electrode modification by thiol derivatives thanks to their high reactivity to the metal. Self assembled monolayers of thioalkyl derivatives on gold represent an important investigation domain in electroanalysis and biosensor developments [16,17].…”
Section: Noble Metal Electrodesmentioning
confidence: 99%
“…There is current interest in gold and platinum electrode modification by thiol derivatives thanks to their high reactivity to the metal. Self assembled monolayers of thioalkyl derivatives on gold represent an important investigation domain in electroanalysis and biosensor developments [16,17].…”
Section: Noble Metal Electrodesmentioning
confidence: 99%
“…In literature, both discotic and calamitic (types of liquid crystalline phases) molecules have been shown to form highly ordered SAMs on gold leading to many interesting properties and phenomena [42][43][44][45][46][47][48]. A number of terminally substituted alkoxycyanobiphenyl compounds such as bromo-, hydroxy-, amino-, carboxy-, epoxy-and olefine-terminated cyanobiphenyls are already known.…”
Section: Introductionmentioning
confidence: 99%
“…Bin et al have carried out the PM-IRRAS studies on the effect of cholesterol on the DMPC bilayer supported at Au electrode [16,17]. Yang et al have reported the electrochemical and IRAS characterization of thiocholesterol SAM [18] and thiocholesterol, fatty acids mixed SAM [19]. To the best of our knowledge, there is no report in the literature on the study of electron transfer properties through the cholesterol monolayers and multilayer films formed on aromatic self-assembled monolayers.…”
Section: Introductionmentioning
confidence: 99%